Chemotherapy Completion in Elderly Women With Ovarian, Primary Peritoneal or Fallopian Tube Cancer—An NRG Oncology/Gynecologic Oncology Group Study. Issue 8 (August 2017) - von Gruenigen, Vivian E.; Huang, Helen Q.; Beumer, Jan H.; Lankes, Heather A.; Tew, William; Herzog, Thomas; Hurria, Arti; Mannel, Robert S.; Rizack, Tina; Landrum, Lisa M.; Rose, Peter G.; Salani, Ritu; et al.
Abstract : (Abstracted from Gynecol Oncol 2017;144:459–467) Older patients with cancer do not tolerate chemotherapy well and suffer more toxicity than do younger women. There is great heterogeneity among patients of a given chronological age in the ability to tolerate treatment.